2022
DOI: 10.1007/s12325-022-02205-2
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of Japanese Dysmenorrhea/Heavy Menstrual Bleeding Patients Treated with Levonorgestrel Intrauterine Delivery System in a Real-World Setting

Abstract: Introduction The present study collected 1-year follow-up patient-reported outcome data from Japanese women with dysmenorrhea and/or heavy menstrual bleeding (HMB) who underwent insertion of the levonorgestrel-releasing intrauterine system (LNG-IUS) 52 mg. We aimed to evaluate the quality of life (QOL) of Japanese women over the course of the investigational period. Methods This was a multicenter, non-interventional, prospective, single-cohort, post-marketing surveillan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The most common of these relate to painful menstruation (also known as dysmenorrhea), heavy menstrual bleeding (HMB), and PMS [ 2 ]. It has been reported that 80% of Japanese women experience dysmenorrhea [ 3 ]; nearly 20% of Japanese women experience HMB [ 4 ]; and more than 25% of Japanese women of reproductive-age experience PMS [ 5 ]. Menstruation-related issues increase women's psychological stress, which can lead to mental health problems such as anxiety and depression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common of these relate to painful menstruation (also known as dysmenorrhea), heavy menstrual bleeding (HMB), and PMS [ 2 ]. It has been reported that 80% of Japanese women experience dysmenorrhea [ 3 ]; nearly 20% of Japanese women experience HMB [ 4 ]; and more than 25% of Japanese women of reproductive-age experience PMS [ 5 ]. Menstruation-related issues increase women's psychological stress, which can lead to mental health problems such as anxiety and depression.…”
Section: Introductionmentioning
confidence: 99%
“…Menstruation-related issues increase women's psychological stress, which can lead to mental health problems such as anxiety and depression. Menstruation-related problems can adversely affect women's quality of life and productivity, resulting in substantial economic and social burdens [ 2 , 4 , 6 ].…”
Section: Introductionmentioning
confidence: 99%